Biodegradable resin film

JP2026167609APending Publication Date: 2026-10-14ACHILLES CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026055393
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-30
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0016】 本願発明は、十分な引裂強度を有しながら日射反射率とともに近赤外線反射率にも優れ、地温上昇が抑制される生分解性樹脂フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167609000001
    Figure 2026167609000001
  • Figure 2026167609000002
    Figure 2026167609000002
Patent Text Reader

Abstract

The present invention aims to provide a biodegradable resin film that has sufficient tear strength while exhibiting excellent near-infrared reflectivity. [Solution] A biodegradable resin film comprising a reflective layer and a colored layer, wherein the reflective layer is made of a resin composition containing a biodegradable aliphatic aromatic polyester resin, a polylactic acid resin, and titanium dioxide having an average particle size of at least 0.8 to 1.3 μm, and is characterized in that, per 100% by mass of the resin composition of the reflective layer, it contains 5% to 30% by mass of the polylactic acid resin, 10% to 50% by mass of titanium dioxide having an average particle size of 0.8 to 1.3 μm, and the total titanium dioxide, including titanium dioxide with an average particle size of 0.8 to 1.3 μm, is 20% to 50% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application invention relates to a film composed of a biodegradable resin, and is particularly a film suitable for agricultural mulch films.

Background Art

[0002] In recent years, films using biodegradable resins have been developed as agricultural mulch films. A biodegradable resin is a resin whose resin components are decomposed into water and carbon dioxide by the action of microorganisms present in soil. Conventional mulch films using olefin-based resins or vinyl chloride-based resins required collection after use for disposal treatments such as recycling or incineration, but by using a biodegradable resin film, the resin components are decomposed in the soil simply by tilling them into the soil together after use, so the aforementioned collection and disposal operations can be omitted, and the burden of agricultural work can be greatly reduced.

[0003] Various types of biodegradable resins are known. For example, aliphatic polyester resins such as polylactic acid (PLA), polybutylene succinate (PBS), and polybutylene succinate adipate (PBSA), aliphatic-aromatic polyester resins such as polybutylene adipate terephthalate (PBAT), and natural polymers such as starch and cellulose are known. Agricultural mulch films are films that cover ridges and the like for growing crops, and are required to have excellent tear strength so that they do not tear during operations such as mechanical spreading with a mulcher or making planting holes, but in general, biodegradable resin films are inferior in physical properties such as tear strength compared to vinyl chloride-based resin films and olefin-based resin films.

[0004] Accordingly, the present applicant conducted studies to improve the tear strength of biodegradable resins, and found that by including a specific amount of polylactic acid-based resin in an aliphatic-aromatic polyester-based resin, the tear strength in the longitudinal direction (machine direction) of the film can be improved, that is, tearing in the longitudinal direction can be suppressed (tear resistance), and has already filed a patent application (Patent Document 1).

[0005] Furthermore, agricultural mulch films are used to promote stable crop growth by providing heat retention, suppressing weeds, and inhibiting soil moisture evaporation. For example, mulch films with a single-layer structure colored transparent or black, and a laminated structure with a reflective layer (white layer) are known. In particular, mulch films equipped with a reflective layer, so-called black and white mulch films, have a reflective layer (white layer) on the surface of a colored layer (black film) that reflects solar radiation (radiation with wavelengths of 300 to 2500 nm), suppressing excessive ground temperature rise in the summer while also possessing the characteristics of mulch films such as weed suppression. For example, Patent Document 2 discloses that, with respect to such a black and white multi-film, the heat shielding properties can be improved by specifying the average particle size of titanium dioxide in the white layer to 0.25 to 0.50 μm.

[0006] However, as shown in Patent Document 2, if the average particle size of titanium dioxide added to the white layer is small, even if the solar reflectance increases, the near-infrared reflectance, which has a greater impact on heat shielding, does not increase. This necessitates the addition of a considerable amount of titanium dioxide, but it has been found that this impairs the film-forming properties of the film. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2025-009794 [Patent Document 2] Japanese Patent Publication No. 2015-65952 [Overview of the Initiative] [Problems that the invention aims to solve]

[0008] Therefore, the present invention aims to provide a biodegradable resin film that has sufficient tear strength, high near-infrared reflectance along with solar reflectance, and excellent ability to suppress ground temperature rise. [Means for solving the problem]

[0009] The inventors of the present invention conducted extensive research to solve the aforementioned problems and, as a result, found that the problems could be solved by using aliphatic aromatic polyester resin and polylactic acid resin as biodegradable resins, and by using titanium dioxide with an average particle size of at least 0.8 to 1.3 μm in the reflective layer, thus completing the present invention.

[0010] In other words, the present invention is a biodegradable resin film comprising a reflective layer and a colored layer, wherein the reflective layer is made of a resin composition comprising a biodegradable aliphatic aromatic polyester resin, a polylactic acid resin, and titanium dioxide having an average particle size of at least 0.8 to 1.3 μm, and is characterized in that, per 100% by mass of the resin composition of the reflective layer, it contains 5% to 30% by mass of the polylactic acid resin, 10% to 50% by mass of titanium dioxide having an average particle size of 0.8 to 1.3 μm, and the total titanium dioxide, including titanium dioxide with an average particle size of 0.8 to 1.3 μm, is 20% to 50% by mass.

[0011] According to the present invention, by including 5% to 30% by mass of polylactic acid resin per 100% by mass of the reflective layer resin composition, a biodegradable resin film is obtained that has sufficient tear strength, and by including 10% to 50% by mass of titanium dioxide with an average particle size of 0.8 to 1.3 μm per 100% by mass of the reflective layer resin composition, and having a total titanium dioxide content of 20% to 50% by mass including titanium dioxide with an average particle size of 0.8 to 1.3 μm, the near-infrared reflectance exceeds 40% along with the solar reflectance, thus providing excellent suppression of ground temperature rise.

[0012] Furthermore, it is preferable that the total titanium dioxide content is 30% by mass or more and 40% by mass or less per 100% by mass of the resin composition of the reflective layer of the present invention, and that the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm is equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm.

[0013] If the total titanium dioxide content is 30% by mass or more and 40% by mass or less, and the amount of titanium dioxide with an average particle size of 0.2 to 0.4 μm is equal to or greater than the amount of titanium dioxide with an average particle size of 0.8 to 1.3 μm, the brightness (L* value) on the reflective layer side of the film can be set to 85 or higher.

[0014] Furthermore, the reflective layer of the present invention comprises a surface reflective layer and an intermediate reflective layer, wherein the total titanium dioxide content of the surface reflective layer is 30% by mass or more and 40% by mass or less based on 100% by mass of the resin composition, and it is preferable that the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm is equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm.

[0015] According to this configuration, the brightness (L* value) of the surface reflective layer can be set to 85 or higher. [Effects of the Invention]

[0016] The present invention provides a biodegradable resin film that has sufficient tear strength, excellent solar reflectance and near-infrared reflectance, and suppresses ground temperature rise. [Modes for carrying out the invention]

[0017] The present invention is a biodegradable resin film comprising a reflective layer and a colored layer.

[0018] The reflective layer of the present invention is made of a resin composition containing a biodegradable aliphatic aromatic polyester resin, a polylactic acid resin, and titanium dioxide. Here, the resin composition referred to in the present invention is a mixture of resin components such as biodegradable aliphatic aromatic polyester resin and polylactic acid resin, titanium dioxide, and other additives, and the resin composition is formed into a film to form a reflective layer.

[0019] The reflective layer of the present invention includes a biodegradable aliphatic aromatic polyester resin and a polylactic acid resin as resin components.

[0020] Examples of the aliphatic-aromatic polyester resin of the present invention include polybutylene adipate terephthalate resins, polybutylene terephthalate alkylate resins, and polybutylene succinate terephthalate resins. In particular, polybutylene adipate terephthalate (PBAT) is preferred in terms of film-forming property and flexibility. Polybutylene adipate terephthalate (PBAT) is formed by a polycondensation reaction between a dicarboxylic acid component consisting of adipic acid and terephthalic acid and a diol component consisting of 1,4-butanediol, and may further contain other components. For example, other diol components may be included. Examples of other diol components include 2,3-butanediol, 1,3-butanediol, 1,4-pentanediol, 2,4-pentanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, diethylene glycol, and the like.

[0021] The polylactic acid resin of the present invention is not particularly limited as long as it is a condensate of lactic acid (polylactic acid (PLA)), and it may be a poly-L-lactic acid resin, a poly-D-lactic acid resin, or a mixture thereof (for example, a stereocomplex polylactic acid resin obtained by mixing a poly-L-lactic acid resin and a poly-D-lactic acid resin).

[0022] Moreover, as the resin component, a resin other than the aliphatic-aromatic polyester resin and the polylactic acid resin may be contained. Examples thereof include biodegradable aliphatic polyester resins such as polybutylene succinate (PBS), polyethylene succinate (PES), polybutylene succinate adipate (PBSA), polycaprolactone (PCL), polyglycolic acid (PGA), polyethylene adipate, polybutylene adipate, polyhydroxy adipate, and polycyclohexylene dimethyl adipate (alicyclic polyester), and derivatives thereof, and one type or a mixture of two or more types may be used.

[0023] In the present invention, the polylactic acid-based resin is contained in an amount of 5% by mass or more and 30% by mass or less with respect to 100% by mass of the resin composition constituting the reflective layer. When the polylactic acid-based resin is less than 5% by mass, the tear strength in the machine direction (MD) of the film decreases, and when the polylactic acid-based resin exceeds 30% by mass, the tear strength decreases not only in the machine direction (MD) but also in the transverse direction (TD) of the film. This tendency is prominent when a large amount of titanium oxide, which will be described later, is contained in the resin composition. The tear strength can be determined by the JIS K 6732 method (Elmendorf method). If the tear strength (N / cm) of the film is 100 N / cm or more in both the machine direction (MD) and the transverse direction (TD), the film is less likely to tear or the like when spread over ridges or the like as a mulch film. Further, it is more preferably 200 N / cm or more.

[0024] In the present invention, the resin composition constituting the reflective layer contains at least titanium oxide having an average particle diameter of 0.8 to 1.3 μm. When the average particle diameter of titanium oxide is less than 0.8 μm or the average particle diameter exceeds 1.3 μm, it becomes difficult to sufficiently obtain the near-infrared reflection effect. In the present invention, titanium oxide having an average particle diameter of 0.2 to 0.4 μm may be used in combination in order to further increase the lightness (L* value) on the reflective layer side. When the average particle diameter of titanium oxide is less than 0.2 μm, the dispersibility in the resin composition is poor, and the lightness (L* value) on the reflective layer side decreases. When it exceeds 0.4 μm, the lightness (L* value) on the reflective layer side decreases. Here, the lightness (L* value) is one of the three attributes of color (lightness, hue, and saturation), indicates the degree of brightness of a color, and can be determined in accordance with JIS Z 8781-4 geometric condition c. The L* value is represented by 0 to 100, and a higher L* value indicates whiteness, while a lower L* value indicates blackness. When the lightness on the reflective layer side of the film is 80 or more, the film has sufficient whiteness, and can exhibit an insect repellent effect and reflect light of wavelengths necessary for photosynthesis. It is more preferably 85 or more, and even more preferably 90 or more.

[0025] The resin composition constituting the reflective layer contains at least 10% to 50% by mass of titanium dioxide with an average particle size of 0.8 to 1.3 μm per 100% by mass, and the total titanium dioxide, including titanium dioxide with an average particle size of 0.8 to 1.3 μm, is at least 20% to 50% by mass. If the total titanium dioxide is less than 20% by mass, the solar reflectance and near-infrared reflectance of the resulting film will be less than 40%. Furthermore, if the total titanium dioxide exceeds 50% by mass, the melt tension decreases, making it impossible to produce a good film, such as one that tears during film formation. Furthermore, if the titanium dioxide content with an average particle size of 0.8 to 1.3 μm is less than 10% by mass, the solar reflectance and near-infrared reflectance of the resulting film will be less than 40%. If it exceeds 50% by mass, the melt tension decreases, making it impossible to produce a good film, such as one that tears during film formation. For example, if the titanium dioxide with an average particle size of 0.8 to 1.3 μm accounts for 20% by mass or more, it is acceptable to use only titanium dioxide with an average particle size of 0.8 to 1.3 μm, or titanium dioxide with an average particle size of 0.2 to 0.4 μm may be used in combination, as long as the total titanium dioxide does not exceed 50% by mass. Furthermore, if the titanium dioxide with an average particle size of 0.8 to 1.3 μm is 10% by mass or more but less than 20% by mass, titanium dioxide with an average particle size of 0.2 to 0.4 μm should be added so that the total titanium dioxide is 20% by mass or more but less than 50% by mass.

[0026] Here, solar reflectance is a value that indicates how much of the energy emitted from the sun, specifically solar radiation with wavelengths of 300 to 2500 nm, is reflected, and can be determined in accordance with JIS A 5759. Near-infrared reflectance is a value that indicates how much of the solar radiation, which is radiation with wavelengths of 780 to 2500 nm, is reflected from the sun, and can be determined by applying JIS A 5759. In the present invention, solar reflectance and near-infrared reflectance are used as indicators of ground temperature rise. According to the applicant, if the solar reflectance and near-infrared reflectance when irradiated from the reflective layer side are 40% or more, the ground temperature rise measured by a solar simulator is significantly suppressed compared to a black and white mulch film using only titanium dioxide with an average particle size of 0.2 to 0.4 μm.

[0027] Furthermore, it is preferable that the total titanium oxide content is 30% to 40% by mass relative to 100% by mass of the resin composition of the film reflective layer. If the total titanium oxide content is 30% by mass or more, the solar reflectance and near-infrared reflectance will be 45% or more. If the total titanium oxide content is 40% by mass or less, good physical properties will be achieved while maintaining high solar reflectance and near-infrared reflectance. Furthermore, it is preferable that the titanium dioxide with an average particle size of 0.2 to 0.4 μm is present in an amount equal to or greater than that of titanium dioxide with an average particle size of 0.8 to 1.3 μm. When the amount of titanium dioxide with an average particle size of 0.2 to 0.4 μm is greater than that of titanium dioxide with an average particle size of 0.8 to 1.3 μm, the brightness of the reflective layer side of the film will be 85 or higher, and a greater insect repellent effect and sufficient reflection of light of wavelengths necessary for photosynthesis can be expected.

[0028] The layer structure of the film of the present invention may consist of two layers laminated together, a surface reflective layer and an intermediate reflective layer, as the reflective layer. The surface reflective layer and the intermediate reflective layer may have the same composition or different compositions. If the surface reflective layer and the intermediate reflective layer have the same composition, they can be considered the same as a single reflective layer of the same composition. The resin components constituting the surface reflective layer and the intermediate reflective layer may be the same as those in the case of a single reflective layer. When the surface reflective layer and the intermediate reflective layer have different compositions, for example, it is preferable that the total titanium dioxide content is 30% to 40% by mass relative to 100% by mass of the resin composition of the film surface reflective layer. If the total titanium dioxide content is 30% by mass or more, the solar reflectance and near-infrared reflectance will be 45% or more. If the total titanium dioxide content is 40% by mass or less, the physical properties will be good while maintaining high solar reflectance and near-infrared reflectance. It is also preferable that the titanium dioxide with an average particle size of 0.2 to 0.4 μm is present in an amount equal to or greater than the titanium dioxide with an average particle size of 0.8 to 1.3 μm. If the amount of titanium dioxide with an average particle size of 0.2 to 0.4 μm is greater than that of titanium dioxide with an average particle size of 0.8 to 1.3 μm, the brightness of the film surface reflective layer will be 85 or higher, and a more effective insect repellent effect and sufficient reflection of light at wavelengths necessary for photosynthesis can be expected.

[0029] The colored layer of the present invention consists of a resin composition containing a biodegradable aliphatic aromatic polyester resin and carbon black. The colored layer is formed by molding this resin composition into a film.

[0030] In the colored layer of the present invention, similar to the reflective layer, the resin component includes a biodegradable aliphatic aromatic polyester resin and a polylactic acid resin, and as the aliphatic aromatic polyester resin, for example, polybutylene adipate terephthalate (PBAT) can be used. In addition, other biodegradable resins may be included, such as those listed for the reflective layer. The resin components constituting the colored layer may be the same as those of the reflective layer, or they may be different. Furthermore, similar to the reflective layer, it is preferable that the colored layer contains 5% to 30% by mass of polylactic acid resin based on 100% by mass of the resin composition. If the polylactic acid resin content is within the range of 5% to 30% by mass, sufficient tear strength of the film can be maintained.

[0031] The carbon black content should be sufficient to provide a weed-suppressing effect. Preferably, it should be less than 20% by mass, and more preferably 1.5 to 15% by mass, relative to 100% by mass of the resin composition constituting the colored layer. If the content is less than 1.5% by mass, the visible light transmittance will be high, making it difficult to obtain a weed-suppressing effect. If it is 20% by mass or more, the processability into film tends to be poor. A content of 1.5 to 15% by mass is preferable because it provides a superior weed-suppressing effect. In order to exhibit a weed-suppressing effect, the visible light transmittance should be 1% or less, preferably 0.7% or less.

[0032] Furthermore, the resin composition constituting the biodegradable film of the present invention may contain other additives as needed, in an amount of about 0 to 5% by mass per 100% by mass of the resin composition that does not impair the effects of the present invention. Examples of other additives include plasticizers, heat stabilizers, lubricants, biodegradation accelerators, biodegradation inhibitors, fillers, and pigments.

[0033] The present invention relates to a film comprising a reflective layer and a colored layer, with a thickness of approximately 10 to 30 μm. The layer ratio of the reflective layer to the colored layer can be appropriately adjusted so that the solar reflectance and near-infrared reflectance are 40% or more, preferably 45% or more, but it is preferable that the thickness of the reflective layer is 50% to 90% of the total thickness. If the thickness of the reflective layer is less than 50%, the solar reflectance and near-infrared reflectance will fall below 40%, and if the thickness of the reflective layer exceeds 90%, the discharge balance of the extruder will be mismatched, making it difficult to manufacture the film.

[0034] The biodegradable film of the present invention can be manufactured using commonly used methods for producing resin films. Examples include T-die molding, inflation molding, and calendering. Furthermore, it can be produced without stretching, or by uniaxial or biaxial stretching. [Examples]

[0035] The present invention will be described below based on the following examples. However, the present invention is not limited to these examples.

[0036] [Resin components] Aliphatic aromatic polyester resin; PBAT (polybutylene adipate terephthalate, manufactured by BASF, trade name "Ecoflex®") Aliphatic polyester resin; PLA (polylactic acid, D-isomer content 2.5% by mass, manufactured by Kaisei Biological Co., Ltd., product name "REVODE110") [Pigments] Titanium dioxide 1 (manufactured by Teika Corporation, product name "JR-1000", average particle size 1 μm) Titanium dioxide-2 (manufactured by Teika Corporation, product name "JR-301", average particle size 0.3 μm) Carbon black (manufactured by Tokyo Ink Co., Ltd., product name "TEP-BP-BLACK1", base resin is a masterbatch with a PBAT content of 35% by mass) [Additives] Unsaturated fatty acid monoamide: Erucic acid amide (manufactured by NOF Corporation, product name "Alflow P-10") Note that the blending amounts in Tables 1 and 2 have been converted to values ​​for pigments only, and the base resin content is added to the blending amount of resin components. In addition, the sum of titanium dioxide 1 and titanium dioxide 2 in the reflective layer is listed as (total titanium dioxide). In Table 2, the amounts of titanium dioxide 1 and titanium dioxide 2 in 100% by mass of the entire resin composition of the reflective layer, including the surface reflective layer and the intermediate reflective layer, and the sum of titanium dioxide 1 and titanium dioxide 2 is listed as (total titanium dioxide).

[0037] Examples 1-16, Comparative Examples 1-6 As shown in Tables 1 and 2, the resin compositions constituting the reflective layer and the colored layer (layer ratio 2:1), or the surface reflective layer, the intermediate reflective layer, and the colored layer (layer ratio 1:1:1), were melt-mixed and pelletized, and then a 2-layer or 3-layer film with a thickness of 20 μm was formed by inflation molding. The mixing ratios of the resin compositions shown in Tables 1 and 2 are in mass percent when the resin composition of each layer—the surface reflective layer, the intermediate reflective layer, and the colored layer—is set to 100% by mass.

[0038] The films obtained in the examples and comparative examples were evaluated as follows. The results are shown in Tables 1 and 2.

[0039] • Solar reflectance This value indicates how much of the solar radiation, specifically the radiation with wavelengths of 300 to 2500 nm, is reflected from the sun. In accordance with JIS A 5759, the spectral reflectance (%) for each wavelength from 300 to 2500 nm was measured using a spectrophotometer (Shimadzu Corporation, product name "UV-3600") when irradiated from the reflective layer side, and the solar radiation reflectance (%) was determined. ◎: 50% or more ○: 45% or more but less than 50% △: 40% or more but less than 45% ×: Less than 40%

[0040] ·Near infrared reflectance This value indicates how much of the energy emitted from the sun, specifically near-infrared radiation with wavelengths of 780 to 2500 nm, is reflected. Following JIS A 5759, the spectral reflectance (%) for each wavelength from 780 to 2500 nm was measured using a spectrophotometer (Shimadzu Corporation, product name "UV-3600") when irradiated from the reflective layer side, and the near-infrared reflectance (%) was determined. ◎: 50% or more ○: 45% or more but less than 50% △: 40% or more but less than 45% ×: Less than 40%

[0041] • Brightness (L* value) The lightness L* of the film's reflective layer surface was measured using a spectrophotometer (Konica Minolta, CM-2500d) in accordance with JIS Z 8781-4 geometric condition c. ◎: 90% or more ○: 85% or more and less than 90% △: 80% or more but less than 85% ×: Less than 80%

[0042] • Solar simulator Each film was stretched over the top surface of a container (14cm long x 14cm wide x 16cm high) in a room adjusted to 23°C. The container was placed in a solar simulator (Seric Co., Ltd., model 'XIL-05A50KS'), and the back surface temperature of the film after irradiation at 20.5A for 30 minutes was measured using a data logger (T&D Corporation, product name 'Ondotori'), and the value of (back surface temperature of each film) - (back surface temperature of the film of Comparative Example 2) was calculated. ◎: Below -0.7℃ 〇: More than -0.7℃, -0.3℃ or less △: More than -0.3℃, below 0℃ ×: Over 0℃

[0043] ·Tear strength The tear strength (N / cm) was calculated by dividing the strength (mN) in the longitudinal (MD) and transverse (TD) directions of the film, measured according to JIS K 6732 (Elmendorf method), by the thickness of the film. 〇:200N / cm or more △: 100 N / cm or more and less than 200 N / cm ×: Less than 100 N / cm

[0044] ·Film forming property During inflation molding, the stability of the bubbles blown out of the die was visually inspected and evaluated as follows. ○: The bubbles were stable without any shaking or meandering, and no holes or tears occurred, resulting in a good quality film. △: The bubbles show some slight wobbling or meandering, but no holes or tears occurred, and a good film was obtained. ×: Film could not be obtained due to the occurrence of holes or tears.

[0045] [Table 1]

[0046] [Table 2]

[0047] According to Examples 1 to 16, films with a solar reflectance and near-infrared reflectance of 40 or more were obtained while maintaining tear strength. Comparative Examples 1 and 2 show that when the titanium dioxide content with an average particle size of 0.8 to 1.3 μm is less than 10% by mass, the near-infrared reflectance is less than 40%. Comparative Example 3 shows that film formation is not possible when the titanium dioxide content with an average particle size of 0.8 to 1.3 μm exceeds 50% by mass. Comparative Example 4 shows that when the total titanium oxide content is less than 20% by mass, the near-infrared reflectance is less than 40%. Comparative Examples 5 and 6 show that when the polylactic acid content is less than 5% by mass or more than 30% by mass, the tear strength decreases.

[0048] Examples 6 to 9 showed that when the total titanium dioxide content was 30% to 40% by mass relative to 100% by mass of the resin composition of the reflective layer, and the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm was equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm, the tear strength was maintained while achieving a near-infrared reflectance of 45% or more, and furthermore, a brightness of 85 or more on the reflective layer side.

[0049] Examples 13 to 16 showed that when the total titanium dioxide content was 30% to 40% by mass relative to 100% by mass of the resin composition of the surface reflective layer, and the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm was equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm, the tear strength was maintained while achieving a near-infrared reflectance of 45% or more, and furthermore, a brightness of 85 or more on the reflective layer side.

[0050] Thus, the biodegradable resin film of the present invention maintains tear strength while having high near-infrared reflectance as well as solar reflectance. Therefore, it can suppress excessive ground temperature rise in the summer caused by near-infrared radiation, making it suitable for agricultural mulch films.

Claims

1. A biodegradable resin film comprising a reflective layer and a colored layer, The reflective layer is made of a resin composition containing a biodegradable aliphatic aromatic polyester resin, a polylactic acid resin, and titanium dioxide with an average particle size of at least 0.8 to 1.3 μm. With respect to 100% by mass of the resin composition of the reflective layer, It contains 5% to 30% by mass of polylactic acid resin. It contains 10% to 50% by mass of titanium dioxide with an average particle size of 0.8 to 1.3 μm. A biodegradable resin film characterized in that the total titanium dioxide content, including titanium dioxide with an average particle size of 0.8 to 1.3 μm, is 20% by mass or more and 50% by mass or less.

2. The total titanium oxide is 30% by mass or more and 40% by mass or less. The biodegradable resin film according to claim 1, characterized in that the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm is equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm.

3. The aforementioned reflective layer consists of a surface reflective layer and an intermediate reflective layer. With respect to 100% by mass of the resin composition of the surface reflective layer, The total titanium oxide content is 30% by mass or more and 40% by mass or less. The biodegradable resin film according to claim 1, characterized in that the content of titanium dioxide with an average particle size of 0.2 to 0.4 μm is equal to or greater than the content of titanium dioxide with an average particle size of 0.8 to 1.3 μm.

Citation Information

Patent Citations

  • Agricultural mulching film

    JP2015065952A

  • Biodegradable resin film

    JP2025009794A